Reconnaissance of Tertiary structures along Nares Strait, Ellesmere Island, Canadian Arctic Archipelago - Mayr, Ulrich; de Vries, Christiaan D. S. (Meddelelser om Grønland. Geoscience, 1982)
In the coastal area of Ellesmere Island between Copes Bay in the south and Cape Baird in the north, at least three phases of Tertiary structural deformation can be distinguished. These are: 1) Paleocene uplifting, 2) Eocene thrusting and 3) strike-slip faulting, probably not younger than Miocene. Uplifting is documented by remnants of a coarse, oligomictic, alluvial conglomerate of Tertiary age. In the southern and central part of the area the conglomerate is over-thrusted by Lower Palaeozoic rocks. Conjugate strike-slip faults are present on Darling Peninsula and northern Judge Daly Promontory. Sinistral displacement along the Judge Daly fault zone is estimated tentatively at 19 km. Thrusting and strike-slip faulting in the Nares Strait area probably correspond to the main phase of the Eurekan orogeny.